EXPLORING THE POSTPARTUM DEPRESSION: INCIDENCE AND EFFECTIVE INTERVENTION STRATEGIES - Muhammad Sajjad; Abida Perveen; Aamir Iqbal; Gull Naz Khan; Rabia Bashir; Ahmed Ikram (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Postpartum depression impacts 10-15% of moms annually. A study conducted in Pakistan examined the frequency and treatment choices for postpartum depression at a rural Punjabi health facility. A quantitative descriptive cross-sectional study was carried out. The study focused on mothers and medical professionals. 120 women and 7 healthcare professionals were selected by convenience sampling. Therapy data for postpartum depression were gathered by a standardized questionnaire with closed-ended questions. A Patient Health Questionnaire was used to assess for depression. The data was analyzed using SPSS 23. Postpartum depression was identified in 0.8% of the examined moms. Various levels of depression symptoms were seen, ranging from mild to severe. Psychosocial support was found to significantly decrease depressed symptoms in healthcare professionals compared to other therapies studied (p = 0.027). Postpartum depression impacts a minority of women, with psychological assistance being the most efficient treatment. Socialization difficulties, sense of inadequacy, and heightened discontent are all indicators of postpartum depression, impacting both the mother and her child. Hospital officials and the Ministry of Health should perform regular screenings for postpartum depression.